Development and validation of the RACER (Readiness for Adult Care in Rheumatology) transition instrument in youth with juvenile idiopathic arthritis - Spiegel, Lynn; Tucker, Lori; Duffy, Karen W.; Lalloo, Chitra; Hundert, Amos; Bourre-Tessier, Josiane; Hazel, Elizabeth; Luca, Nadia; Mosher, Dianne; Nguyen, Cynthia; Stringer, Elizabeth; Victor, Charles; et al. (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Current evidence suggests that many adolescents with juvenile idiopathic arthritis (JIA) do not successfully transfer to adult care, which can result in adverse health outcomes. Although a growing number of clinical programs have been designed to support healthcare transition, there is a lack of psychometrically sound instruments to evaluate their impact on development of transition-related knowledge and skills in youth with JIA. The purpose of this study was to develop and validate RACER (Readiness for Adult Care in Rheumatology), a self-administered instrument designed to measure stages of readiness for key transition-related skills in adolescents with JIA. Methods A phased approach was used to develop and evaluate the validity and reliability of RACER. Phase 1 A was a consensus conference with 19 key stakeholders to inform instrument domains and items. Phase 1B determined initial content validity using a sample of 30 adolescents with JIA and 15 clinical and research experts. Finally, Phase 2 was a prospective cohort study with repeated measures to evaluate the internal consistency, test-retest reliability, construct validity and responsiveness of the instrument within a sample of adolescents with JIA. Results In Phase 1 A, initial item generation yielded a total of 242 items across six domains from the consensus conference, which was subsequently reduced to a 32-item instrument. Phase 1B established the content validity of the instrument in adolescents with JIA. In the Phase 2 study, with a sample of 96 adolescents, the RACER instrument exhibited good internal consistency in five of its six subscales (Cronbach’s α > 0.7), and strong test-retest reliability between the first two administrations (ICC = 0.83). It also showed robust convergent validity by highly correlating with measures of self-management (SMSAG, rho = 0.73) and transition (TRANSITION-Q, rho = 0.76). The RACER was not correlated with unrelated measures (discriminant validity; PedsQL, rho = 0.14). The RACER scores increased significantly over time as expected, supporting measure responsiveness. Conclusions The RACER is a reliable and valid instrument which is sensitive to change for assessing transition readiness in adolescents with JIA.